Investigating Financial Biases that Can Increase Impact on Paying Bills and Saving - Lucy M Delgadillo Ph.D. (Journal of Financial Therapy, 2021)
This article explores financial biases and their relation to financial management behaviors. Using cognitive, evolutionary psychology, and behavioral finance theories, this study suggests that biases can be intentionally used to our benefit. The study shows statistically significant associations between some biases and financial management practices such as paying bills on time and saving regularly in the surveyed sample. The study provides insights into intentionally using financial biases to increase impact and success by helping individuals commit to the best course of action or choose the least costly financial alternative.
Keywords: Behavioral finance; financial biases; saving; spending plan